Gold Medal Swim - Jake Maddox (Stone Arch Books, 2012)
Sam is the best swimmer on his school swim team. When Julien, a new exchange student at school, joins the team near the end of the season, Sam offers to help him practice. But when Sam and Julien have to race against each other in the final meet, only one swimmer can win the gold.
Keywords: Sport Stories -- Sport Stories